PERSEPSI WARTAWAN MENGENAI KODE ETIK JURNALISTIK PASAL SATU (STUDI PADA WARTAWAN KABAR.NEWS) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses journalists 'perceptions of the journalistic code of ethics in article 1. The results of this study are Kabar.news journalists' perceptions of journalistic code of ethics article 1, Kabar.news journalists see journalistic code of ethics as a tool to maintain journalist independence and professionalism. Kabar.news makes journalistic code of ethics as a guideline for values and ethics in work in order to be able to present quality news, Kabar.news journalists view the journalistic code of ethics, especially in article 1, as a principle matter. Then how the journalistic code of ethics article 1 can affect the quality of news. The journalistic code of ethics, especially in article 1, greatly affects the quality of reporting, the code of ethics plays an important role in the correctness of the information and as an ethical guideline for journalists in conveying information that is in accordance with the actual facts. So that the news published has more weight and can be trusted by the public.